Proximal balloon occlusion versus distal filter protection in carotid artery stenting: A meta‐analysis and review of the literature. Issue 5 (12th November 2016) - Omran, Jad; Mahmud, Ehtisham; White, Christopher J.; Aronow, Herbert D.; Drachman, Douglas E.; Gray, William; Abdullah, Obai; Abu‐Fadel, Mazen; Firwana, Belal; Mishkel, Gergory; Al‐Dadah, Ashraf S.
Abstract : Introduction: Carotid artery stenting (CAS) is typically performed using embolic protection devices (EPDs) as a means to reduce the risk of procedure‐related stroke. In this study, we compared procedural morbidity and mortality associated with distal (D‐EPD) vs. proximal (P‐EPD) protection. Methods: MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were queried from January 1998 through May 2015. Only studies comparing (D‐EPD) and (P‐EPD) were included. Two independent reviewers selected and appraised studies and extracted data in duplicate. Random‐effects meta‐analysis was used to pool outcomes across studies. Heterogeneity of treatment effect among studies was assessed using the I 2 statistics. Publication bias was assessed using inspection of funnel plots. The primary endpoints included 30‐day mortality and stroke. Secondary endpoints included new cerebral lesions on diffusion‐weighted magnetic resonance imaging (DW‐MRI) and contralateral lesions on DW‐MRI. Results: A total of 12, 281 patients were included from 18 studies (13 prospective and 5 retrospective) comparing (D‐EPD) and (P‐EPD) in the setting of CAS. The mean patient age was 69 years and 64% of patients were male. No evidence of publication bias was detected. There was no significant difference between the two modalities in terms of the risk of stroke (risk difference [RD] 0.0, 95% confidence interval [CI] −0.01 to 0.01) or mortality (RD 0.0, 95% CI −0.01 to 0.01) nor was there any difference in the incidence of new cerebral lesions on DW‐MRI or contralateral DW‐MRI lesions. Conclusions: In patients undergoing CAS, both D‐EPD and P‐EPD provide similar levels of protection from peri‐procedural stroke and 30 days mortality. © 2016 Wiley Periodicals, Inc.